All-electrical creation and control of spin-galvanic signal in graphene and molybdenum ditelluride heterostructures at room temperature - Anamul Md. Hoque (Nature Portfolio, 2021)
By using 2D materials heterostructures it is possible to exploit the properties of both materials at the interface, for instance, spin-dependent transport for application in spintronic devices. Here, using a heterostructure of MoTe2/Graphene the authors demonstrate a proximity induced spin-galvanic effect which can be controlled by the gate voltage.